2015
DOI: 10.1210/jc.2014-3697
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Events, Secondary Intracranial Tumors, and Mortality After Radiotherapy for Nonfunctioning Pituitary Adenomas: A Subanalysis From the Dutch National Registry of Growth Hormone Treatment in Adults

Abstract: The incidence of secondary intracranial tumors and mortality did not differ between IRR and non-IRR patients. However, a CVE was found significantly more frequently in IRR men but not in women. Further research into the long-term effects of cranial radiotherapy seems mandatory. The potential risks of radiotherapy have to be taken into account when radiotherapy is considered in NFPA patients, and long-term follow-up is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 38 publications
2
42
1
Order By: Relevance
“…However, after correction for pituitary dysfunction, this association was no longer significant, suggesting that the observed increase in premature mortality is mediated by RT‐induced hypopituitarism rather than an independent effect of RT itself. These data are consistent with findings from Tomlinson and other older studies,16, 36 as well as the more recent van Varsseveld and Oxford studies 17, 35. There was a trend towards an increased risk of cerebrovascular death compared to nonirradiated patients, but this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, after correction for pituitary dysfunction, this association was no longer significant, suggesting that the observed increase in premature mortality is mediated by RT‐induced hypopituitarism rather than an independent effect of RT itself. These data are consistent with findings from Tomlinson and other older studies,16, 36 as well as the more recent van Varsseveld and Oxford studies 17, 35. There was a trend towards an increased risk of cerebrovascular death compared to nonirradiated patients, but this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
“…RT itself has been independently associated with increased mortality risk in the treatment of both acromegaly and NFPA,9, 11 with the higher death rate largely attributable to cerebrovascular disease. However, an independent association between RT and mortality in NFPA has not been consistently replicated across studies, and both the Tomlinson study and the Dutch study of van Varsseveld found no increase in mortality between irradiated and nonirradiated patients 16, 17. Further confounders in this area include treatment‐associated effects on mortality; overzealous hydrocortisone (HC) replacement in patients with adrenocorticotropic hormone (ACTH) deficiency has been associated with increased mortality, both in NFPA and acromegaly 11, 18.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported by others (3,4,6,17). Although radiotherapy has positive effects on tumor control, concerns have been raised about long-term side effects such as hypopituitarism and increased risks of cerebrovascular events or secondary intracranial tumors (2,5,(31)(32)(33)(34). It has been postulated that GH-RT may enhance this risk of secondary tumors because of the potential mitogenic effects of GH and IGF-1 and reports of increased risk of secondary tumors in childhood cancer survivors or children treated with GH-RT (13,(35)(36)(37).…”
Section: Discussionsupporting
confidence: 77%
“…In one study, mortality due to malignancies was not elevated in adults receiving GH-RT compared to the background population (27). In another study, the occurrence of secondary intracranial tumors did not differ between irradiated and nonirradiated NFPA patients (1.1 vs 0.6%), but the risk of cerebrovascular events was increased in irradiated men (31). Overall, as discussed in a recent review, fatal and nonfatal malignancies do not appear to be more prevalent in GHtreated adults compared to the general population, and also not in previously irradiated patients (11,18).…”
Section: Discussionmentioning
confidence: 92%
“…Although no other specific analyses of the risk of intracranial haemorrhage were identified, the reported incidence appears low. Recent data from a large national registry suggest that radiotherapy for nonfunctioning pituitary adenoma, a frequent cause of AO‐GHD, may increase the cerebrovascular event risk in men but not women, an observation that warrants further research …”
Section: Discussionmentioning
confidence: 74%